2015
DOI: 10.1071/an13284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing time on the quality of dry-cured ham obtained from a native pig breed (Chato Murciano)

Abstract: The compositional and sensory parameters of Chato Murciano dry-cured ham at different ripening times (14, 18, 22 and 24 months of processing) were studied. A sensory consumer study of dry-cured ham with a short ripening stage (14 months of processing) and a similar ham with a long ripening stage (22 months of processing) was carried out. Dry-cured hams remained in the ripening stage at 18−20°C and 70–75% relative humidity. The different processing times studied had no effect on the ash, intramuscular fat, sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 36 publications
5
13
0
Order By: Relevance
“…Processing time affects fatty acid content in all lipid fractions, showing a NL (p < 0.001) and PL (p < 0.001) decrease, and a FFA increase (p < 0.001). A similar evolution was observed in dry-cured ham from other breeds [17,19], as well as in CM dry-cured loin [8]. The main changes take place until month 18 of processing, showing variations of −40%, −88% and +516% in NL, PL and FFA respectively.…”
Section: Total Fatty Acid Compositionsupporting
confidence: 76%
See 2 more Smart Citations
“…Processing time affects fatty acid content in all lipid fractions, showing a NL (p < 0.001) and PL (p < 0.001) decrease, and a FFA increase (p < 0.001). A similar evolution was observed in dry-cured ham from other breeds [17,19], as well as in CM dry-cured loin [8]. The main changes take place until month 18 of processing, showing variations of −40%, −88% and +516% in NL, PL and FFA respectively.…”
Section: Total Fatty Acid Compositionsupporting
confidence: 76%
“…In addition, derived products with clearly distinctive qualities are obtained from the native pig breeds of southern Europe [7]. For this reason, CM dry-cured products are well accepted by consumers [8]. Previous works have described the fatty acids and lipolysis of CM dry-cured loin [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the high adipogenic potential, which is typical of native pig breeds such as the CM. Several studies of dry‐cured loin and ham have confirmed the effect of the IMF content on the sensory characteristics of the product . Therefore, this parameter has a great influence in the sensorial perception of the dry‐cured loin.…”
Section: Resultsmentioning
confidence: 92%
“…Although previous works studied the sensory quality of CM dry‐cured loin and ham , greater knowledge of the fatty acid concentration and lipolysis is necessary because these are among the parameters that most affect product quality.…”
Section: Introductionmentioning
confidence: 99%